2012
DOI: 10.1523/jneurosci.5123-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Effects of Highly Pathogenic H5N1 Influenza Virus Infection in the CNS of Mice

Abstract: The A/VN/1203/04 H5N1 influenza virus is capable of infecting the CNS of mice and inducing a number of neurodegenerative pathologies. Here, we examined the effects of H5N1 on several pathological aspects affected in parkinsonism, including loss of the phenotype of dopaminergic (DAergic) neurons located in the substantia nigra pars compacta (SNpc), expression of mono- and indolamines in brain, alterations in SNpc microglia number and morphology, and expression of cytokines, chemokines and growth factors. We fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
103
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 73 publications
(86 reference statements)
4
103
1
3
Order By: Relevance
“…Moreover, TNF-α reduced neurogenesis in adult rat hippocampus and promoted apoptosis in adult rats. Elevated levels of IL-6 reduce proliferation, gliogenesis, and neurogenesis and increase apoptosis in rat hippocampus by reducing soluble factors, such as the protein sonic hedgehog, which is known to promote neuronal differentiation [31]. In agreement with our Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, TNF-α reduced neurogenesis in adult rat hippocampus and promoted apoptosis in adult rats. Elevated levels of IL-6 reduce proliferation, gliogenesis, and neurogenesis and increase apoptosis in rat hippocampus by reducing soluble factors, such as the protein sonic hedgehog, which is known to promote neuronal differentiation [31]. In agreement with our Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Free dopamine triggers an inflammatory response in the brain characterized by the increase of cytokines and chemokines [31] leading to microgliosis. Inflammatory mediators can exert both beneficial and deleterious effects in the central nervous system (CNS); immune protection and aid in removal of dead neurons are the beneficial ones.…”
mentioning
confidence: 99%
“…At the steady state, microglia perform continuous surveillance of the CNS for danger signals and provide trophic support to neurons (46). When activated, microglia proliferate, form nodules to surround areas of damage, and secrete cytokines/chemokines to recruit immune cells (47)(48)(49)(50)(51)(52)(53). Despite different triggering events, microglia activation is a major characteristic of neurodegenerative conditions, including Alzheimer's disease, Parkinson's diseases, traumatic brain injury, and multiple sclerosis (54)(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…Comparable central nervous system (CNS) involvement in mice by the inflammatory response in the lung and in different regions of the brain (brainstem, substantia nigra, striatum, and cortex) has been described in case of infl uenza H5N1 virus infection. [66] CNS involvement during influenza includes a variety of syndromes, more often described in children than in adults, and the major clinical entities are encephalitis or encephalopathy. [67] In etiological studies of encephalitis, influenza A and/or B have been identified in up to 10% of pediatric cases.…”
Section: Review Articlementioning
confidence: 99%